Planar superconducting toroidal metamaterial : a source for oscillating vector-potential? - Savinov, V. (2018)
We demonstrate the first superconducting metamaterial that can exhibit a profound toroidal dipolar resonance. Quantum behaviour of the superconductor and toroidal excitation of the metamaterial are both necessary prerequisites for observing the time-dependent Aharonov-Bohm effect.